Physician Manpower and Distribution in Florida, 1976 - Penrod, Kenneth E.; State Univ. System of Florida, Tallahassee ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
This study, requested by the Community Hospital Education Council, was undertaken to provide guidance in the allocation of state resources in support of internship and residency programs. An attempt is made to establish goals of physician manpower in each of the major specialty groups and to indicate the excess or deficit now extant in Florida. Findings are: (1) 884 more general/family practitioners are needed; (2) 774 more internists are needed; (3) 165 general pediatricians are needed; (4) more psychiatrists, anesthesiologists, plastic surgeons and otorhinolaryngologists are needed; and (5) there is an adequate supply, and in some cases an oversupply, in other specialty areas of medicine. (Author/KE)
Availability: State University System of Florida, 107 W. Gaines Street, Tallahassee 32304.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Demography; Educational Needs; Geographic Distribution; Higher Education; Labor Needs; Medical Education; Physicians; Statewide Planning; Surveys; Tables (Data); Florida; Reports, Research